Twentieth century fashion in detail - Wilcox, Claire; Mendes, Valerie D (New York, NY : Victoria & Albert Museum, 2009)
Designers include: Christobal Balenciaga, Pierre Balmain, Pierre Cardin, John Cavanagh, Coco Chanel, Sybil Connolly, André Courrèges, Culture Shock, (Yuzun Koga & Jeannie Macarthur), Jean Dessès, Christian Dior, Matilda Etches, Mariano Fortuny, Mr. Freedom (Tommy Roberts), John Galliano, Bill Gibb, Hubert de Givenchy, Madame Grès, Katherine Hamnett, Norman Hartnell, Jaccques Heim, Charles James, Christian Lacroix, Jeanne Lanvin, Lucile (Lady Duff Gordon), Eva Lutyens, Mainbocher, Lun-Na Menoh (Atsuko Shimizu), Digby Morton, Jean Muir, Pablo & Delia, Paquin, Paul Poiret, Antony Price, Mary Quant, Zandra Rhodes, Yves Saint Laurent, Elsa Schiaparelli, Victor Steibel, Emanuel Ungaro, Phillipe Venet, Madeleine Vionnet, Vivienne Westwood, Charles Frederick Worth, Yuki.
boek